2010
DOI: 10.1002/pon.1679
|View full text |Cite
|
Sign up to set email alerts
|

Sexual functioning in long‐term survivors of Hodgkin's lymphoma

Abstract: Consistent with previous studies, HL survivors reported high rates of current sexual problems. However, no differences in sexual problems or sexual satisfaction were found between survivors and controls. Results indicate that over the long term, survivors' sexual functioning does not differ from noncancer controls. Findings underscore the importance of including healthy control groups to determine whether difficulties reported by cancer survivors can be attributed to cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
3
25
2
Order By: Relevance
“…This study contributes new knowledge in this field, since the AYA cancer survivors in this study actually do express lower satisfaction with their sexual functions than the control group of the study. However, the results in this study are incongruent with some previous studies that included a control group but reported no significant difference between the study groups and the controls [12,30].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This study contributes new knowledge in this field, since the AYA cancer survivors in this study actually do express lower satisfaction with their sexual functions than the control group of the study. However, the results in this study are incongruent with some previous studies that included a control group but reported no significant difference between the study groups and the controls [12,30].…”
Section: Discussioncontrasting
confidence: 56%
“…A total of 122 participants declined participation, and 67 did not complete the questionnaire. The study group consisted of 285 survivors of cancer during adolescence and young adulthood, with the mean age of 28 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and the control group consisted of 255 participants with the mean age of 28 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. There were no differences between the groups, except regarding education, where the controls had a significantly higher educational level than the cancer survivors.…”
Section: Resultsmentioning
confidence: 99%
“…No association with time since diagnosis, disease stage, or CT were detected (Recklitis et al , 2010). Compared with this study, the strength of our analysis is the fact that we had information on SX and patient characteristics before starting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term sexual dysfunction has been documented in patients with solid tumours (Schover 2005; Webber et al , 2011). In contrast, only few data are available for SX in lymphoma survivors and most of them are limited to the follow-up period (Kornblith et al , 1992a; Kornblith et al , 1992b; Abrahamsen et al , 1998; Heutte et al , 2009; Kiserud et al , 2009; Recklitis et al , 2010). In our analysis, having information on SX and patients characteristics already before starting treatment allows an investigation of possible correlations between these characteristics and SX independently of Hodgkin Lymphoma (HL) therapy.…”
mentioning
confidence: 99%
“…Up until today, only a few cross‐sectional studies have reported on sexual problems among female HL survivors with 65% reporting decreased sexual activity and 56% decreased sexual interest (Recklitis et al . ). In patients with HL, sexual function is associated with POF (Schover , Graziottin , Millheiser et al .…”
Section: Introductionmentioning
confidence: 97%